(untitled) (Fourth World Journal, 2025)
This article examines the psychological warfare tactics used against the Indigenous Peoples Movement in conflicts with modern states, stressing the importance of challenging mainstream media narratives that seek to assimilate indigenous cultures. It discusses the role of propaganda, civil society, and the necessity of creating a new culture based on mutual respect. It further explores the impact of financial and psychological dependence on indigenous peoples, the challenges faced by indigenous lobbyists at the UN, and the barriers to implementing indigenous human rights within the UN system. It critiques the exclusion of Fourth World nations from UN decision-making processes and advocates for new institutions to address indigenous rights, highlighting the UN’s role in perpetuating human rights abuses against indigenous populations.Pending